A dynamic expression pattern of sGalpha(i2) protein during early period of postnatal rat brain development. - López-Aranda, Manuel Francisco; López-Téllez, Juan Félix; Blanco-Calvo, Eduardo; Masmudi-Martín, Mariam; Navarro-Lobato, Irene; Khan, Zafaruddin (Elsevier, 2008)
The function of sG alpha i2 protein in central nervous system is not well understood. Therefore to explore the possible role of this protein in postnatal brain development, we have analyzed the protein expression pattern of brain obtained from rats of postnatal day 0 (P0) to P90 by dot-blots and immunocytochemistry techniques. In dot-blots, both nuclear and membrane fractions showed a gradual decrease from P0 to P60. Highest protein level was observed at the age of P0. There was also a trend of decline in the sG alpha i2 protein from P0 to P90 in brain sections stained by immunocytochemistry method. At P0, the protein labeling was highest in cerebral cortex, hippocampus, cerebellum and mitral cell layer. In cerebral cortex, a drop in the immunolabeling of sG alpha i2 protein was observed at P3, which was significantly increased at the age of P5. However, in striatum and olfactory tubercle, it was maintained through P0-P10 and P0-P5, respectively. Thalamus was one of the areas where labeling was not as strong as cortex, hippocampus or striatum. In contrary to other areas, immunostaining of sG alpha i2 in corpus-callosum and lacunosum-moleculare was not seen at P0 and appeared in advanced postnatal ages. A detectable level of sG alpha i2 protein was observed at P5 in carpus-callosum and at P20 in lacunosum-moleculare. A high level of sG alpha i2 protein in the period when cellular layer organization and synaptic innervations, synaptic connections and maturation take place, suggests for a potential role of this protein in the early postnatal brain development. (C) 2008 ISDN. Published by Elsevier Ltd. All rights reserved.
https://openpolicyfinder.jisc.ac.uk/id/publication/12557
Keywords: Sistema nervioso central; Inmunohistoquímica; Immunohistochemistry; Dot-blots; G protein; sGai2 protein; Postnatal development